§ 3.

                  38.
f(x) g(x).
38.01.
f(x) = 2x3 52 + 1;
38.02.
g(x) = 2x3 x2 + 5 + 4;
38.03.
f(x) = 8x3 + 422 + 37 12;
38.04.
g(x) = 2x3 + 7x2 + 7 + 2;
38.05.
f(x) = 6x3 + 2 20 12;
38.06.
g(x) = 5x3 2x2 2 1;
38.07.
f(x) = 2x3 + 32 2 3;
38.08.
g(x) = 2x3 + x2 + 4 2;
38.09.
f(x) = 2x3 32 + 3 15;
38.10.
g(x) = x3 + x2 + 11;
38.11.
f(x) = 3x3 42 + 2 2;
38.12.
g(x) = 2x3 + 3x2 + 2 + 2;
38.13.
f(x) = x3 + 32 + 6;
38.14.
g(x) = x3 + x2 2 1;
38.15.
f(x) = 2x3 + 32 + 6 4;
38.16.
g(x) = x3 6x2 + 15 14;
38.17.
f(x) = x3 62 + 11 6;
38.18.
g(x) = 8x3 12x2 2 + 3;
38.19.
f(x) = 6x3 + 172 23 70;
38.20.
g(x) = x3 11x2 + 38 40;
38.21.
f(x) = 6x3 352 8 + 12;
38.22.
g(x) = 8x3 70x2 + 101 21;
38.23.
f(x) = x3 62 + 6 + 10;
38.24.
g(x) = x3 6x2 + 9 + 104;
38.25.
f(x) = x3 62 + 11 11;
38.26.
g(x) = x3 3x2 2 + 7;
38.27.
f(x) = 2x3 32 200 99;
38.28.
g(x) = x3 70x2 + 101 21;
38.29.
f(x) = 3x3 2 27 + 9;
38.30.
g(x) = 8x3 12x2 + 6 1;
38.31.
f(x) = 5x3 + 182 10 8;
38.32.
g(x) = 2x3 5x2 8 + 20;
38.33.
f(x) = x3 + 2 4 + 2;
38.34.
g(x) = x3 8x2 + 23 24;
 
38.35.
f(x) = x3 + 32 2 1;
38.36.
g(x) = x3 3x2 6 + 20.

\..\

                              Copyright © 2008-2009 ..   . .